Twelve Months Post-treatment Results From the Norwegian Version of Improving Access to Psychological Therapies - Sæther, Solbjørg Makalani Myrtveit; Knapstad, Marit; Grey, Nick; Smith, Otto R. F. (Frontiers in Psychology, 2019)
Objectives Prompt Mental Health Care (PMHC) is the Norwegian version of the England’s Improving Access to Psychological Therapies (IAPT). Both programs have been associated with substantial symptom reductions from pre- to post-treatment. The present study extends these findings by investigating symptom levels at 12 months post-treatment, as well as treatment outcome in relation to low- vs. high-intensity treatment forms. Design and Outcome Measures A prospective cohort design was used. All participants (n = 1530) were asked to complete the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 questionnaire (GAD-7) at baseline, before each session during treatment, at final treatment, and at 12 months post-treatment. Cohen’s d was used as effect size measure. Sensitivity analyses were conducted to examine the impact of the high missing data rates at post-treatment (≈44%) and 12 months post-treatment (≈58%). Results A large symptom reduction was seen from baseline to 12 months post-treatment for both PHQ (d = −0.98) and GAD (d = −0.94). Improvements observed at post-treatment were largely maintained at 12 months post-treatment (PHQ (Δd = 0.10) and GAD (Δd = 0.09). Recovery rates decreased only slightly from 49.5% at post-treatment to 45.0% at follow-up. Both low- and high-intensity treatment forms were associated with substantial and lasting symptoms reductions (−1.26 ≤ d ≤ −0.73). Sensitivity analyses did not substantially alter the main results. Conclusion The findings suggest long-lasting effects of the PMHC program and encourage the use of low-intensity treatment forms in PMHC like settings.